Evaluation of maturity stage, postharvest storage temperature and packaging system towards maximising quality retention of straw mushroom [Volvariella volvacea (Bul.) Singer] - Mohd Joha, Nur Sakinah (2019)
Volvariella volvacea, also known as straw mushroom is edible. It has attracted growing attention in Malaysia due to short cropping duration and provides distinct flavour and pleasant taste. However, this mushroom is highly perishable and has very short shelf life within 1-2 days under ambient temperature. The harvesting time and maturity of V. volavacea are important factors to maintain the quality of the mushroom. As the succeeding stages that follow the immature stage was particularly fast, farmers usually collected both immature and mature stage at harvest. Thus the objective of the first experiment was to evaluate the quality, antioxidant activity, and health risk assessment of V. volvacea at both stages. The mushrooms was cultivated on composted EFB and harvested after a week at immature (button stage) and mature (veil open stage). Button stage mushroom showed significantly higher firmness, and higher antioxidant activity with lower IC₅₀ of DPPH. In addition, button stage provides higher content of glutamic acid. However, both stages were within safety limit dietary intake from heavy metals. Thus, based on the results of the first experiment, button stage was further selected for the second experiment. The objective of the second experiment was to determine the postharvest qualities and antioxidant activity at different storage temperatures (10, 15 ºC, and room temperature (RT)) and storage durations (0, 2, 4, 6 and 8 days). The V. volvacea was cultivated according to Experiment 1 and the button stage were harvested for storage in perforated polyethylene (PE) plastic films. Volvariella volvacea stored at 15 °C showed significantly lowest in the percentage of weight loss, no veil opening, retains higher firmness, inhibits browning and PPO enzyme activity for about 6 days. The V. volvacea stored at 10 ºC showed chilling injury symptoms and loss its postharvest quality.However, there was a sharp drop of DPPH activity when stored at RT. The tissue ultrastructure of V. volvacea at 15 ºC showed no major changes as compared to 10 ºC and RT where there were tissue shrinkage and bacterial contamination. Thus the mushrooms were best stored at 15 ºC for the next experiment.The experiment was then expanded to the third objective which was to examine the optimum packaging systems (perforation, PVC film wrap, vacuum and control) applied to V. volvacea at different storage durations (0, 2, 4, 6 and 8 days) and stored at 15 ºC. The cultivation and harvesting method was conducted as previous. The mushrooms were packed in 4 different packaging systems. PVC film was shown to maintain significantly higher firmness, lower weight loss, high DPPH radical scavenging activity, lower browning degree and PPO enzyme activity compared to other packaging. Furthermore, there was less damages and shrinkage of ultrastructure tissue when stored in PVC film packaging showed. Overall, button stage of V. volvacea were best stored at 15°C storage temperature in PVC film packaging system which could retain their quality throughout 6 days storage periods and extend their shelf life.